(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
In this article, with the help of the educational and professional program, the specificity and features of the professional development of future managers of the aviation industry are analyzed. Professional development of a specialist is of particular importance in conditions of growth at a rapid pace in all spheres of world life. An important feature of modernity is the growing interdependence of economies of different countries, mutual integration, the development of economic relations, global informatization and the rapid development of cultural interchange between countries and tourism. Therefore, an important direction of competitiveness of any enterprise, in particular, the airline and the state in general, is the training of highly qualified specialists who are able to quickly adapt to the rapidly developing conditions of the present. The main tool for training future specialists is higher education, which should create the necessary conditions for proper training of a specialist who aspires to self-development and self-improvement for successful professional activity and further for competitiveness in the labor market. The basis for assessing the quality of higher education and vocational training are the standards of higher education, as well as the quality of educational activities of higher education institutions, regardless of their types, levels of accreditation and forms of education. The standard of higher education determines the content and results of higher education for each level and within a separate specialty, and the standard of educational activity determines the minimum requirements for personnel, educational, methodical, material, technical and informational support of the educational process. On the basis of the educational and professional program, a higher education institution for each specialty develops a curriculum that determines: the list and scope of academic disciplines in ECTS credits; sequence of study of disciplines; forms of training sessions and their volume; study schedule; forms of current and final control. Analyzing the level of professional training of the specialty “Management” in the Flight Academy of NAU, we can say about some shortcomings that have a significant impact on the future professional development of aviation industry management specialists, which include: the level of interdisciplinary integration; low level of organization of independent work of students and insufficient control over its implementation; no hours for individual work with students; low level of implementation of information technology in the educational process; weak connection of theoretical professional training with practical activities.